The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1542/peds.2015-4544
|View full text |Cite
|
Sign up to set email alerts
|

Parental Country of Birth and Childhood Vaccination Uptake in Washington State

Abstract: BACKGROUND: Underimmunization of certain immigrant populations can place them at high risk of experiencing vaccine-preventable disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In response to the steady decline in naturally acquired HAV immunity especially in children in many parts of the world, some countries have introduced universal childhood vaccination programmes in recent years 9 , 17 – 20 , 63 , 64 . The WHO suggests a vaccination strategy according to the HAV endemicity of the particular region 65 – 68 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the steady decline in naturally acquired HAV immunity especially in children in many parts of the world, some countries have introduced universal childhood vaccination programmes in recent years 9 , 17 – 20 , 63 , 64 . The WHO suggests a vaccination strategy according to the HAV endemicity of the particular region 65 – 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the relatively high infectivity of HAV together with a low rate of HAV immunity (lack of herd immunity), the outbreak potential in children is significant. Thirdly, HAV infections in children are mainly mild or even asymptomatic but are still quite common, so that numerous infections can go unnoticed which further promotes the spread of HAV 4 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural beliefs, health beliefs, prior experiences, and language proficiency of the host country contribute to the lower likelihood that FSU immigrant women and older people (less literature is available about male FSU immigrants) choose to participate in preventative activities such as diagnostic screenings [73][74][75][76]. In the USA, FSU immigrants are less likely to immunize their children [77]. Although older FSU immigrants have multiple chronic conditions, they seldomly engage in preventative actions such as physical activity [78] and may lack the skills to select healthy foods due to unfamiliarity with the foods and food labels in the host country [54].…”
Section: Health Literacy Relevant Issues Among Fsu Immigrants In Thementioning
confidence: 99%
“…A prospective study in a refugee clinic in Australia between 2000 and 2002 showed that, only 5% of 136 East African pediatric patients had a documented vaccination, and only 15% had protecting levels of serum tetanus antitoxin10. In a retrospective study conducted in the American immunization database between 2008 and 2013, it was emphasized that a variety of different cultural subgroups with a non-American background had incomplete immunization, and the risk of the disease was significantly higher especially in cultures that refused vaccination 11 …”
Section: Discussionmentioning
confidence: 99%